Analysis of the nasopharyngeal microbiome and respiratory pathogens in COVID-19 patients from Saudi Arabia - Muhammad Yasir; Hessa A. Al-Sharif; Tagreed Al-Subhi; Anees A. Sindi; Diyaa H. Bokhary; Mai M. El-Daly; Bandar Alosaimi; Maaweya E. Hamed; Asad Mustafa Karim; Ahmed M. Hassan; Mustafa M. AlShawdari; Maha Alawi; et al. (Elsevier, 2023)
Background: Infection with SARS-CoV-2 may perturb normal microbiota, leading to secondary infections that can complicate the viral disease. The aim of this study was to probe the alteration of nasopharyngeal (NP) microbiota in the context of SARS-CoV-2 infection and obesity and to identify other respiratory pathogens among COVID-19 cases that may affect patients' health. Methods: A total of 107 NP swabs, including 22 from control subjects and 85 from COVID-19 patients, were processed for 6S amplicon sequencing. The respiratory pathogens causing secondary infections were identified by RT-PCR assay, using a kit that contained specific primers and probes combinations to amplify 33 known respiratory pathogens. Results: No significant (p > 0.05) difference was observed in the alpha and beta diversity analysis, but specific taxa differed significantly between the control and COVID-19 patient groups. Genera of Sphingomonas, Kurthia, Microbacterium, Methylobacterium, Brevibacillus, Bacillus, Acinetobacter, Lactococcus, and Haemophilus was significantly abundant (p < 0.05) in COVID-19 patients compared with a healthy control group. Staphylococcus was found in relatively high abundance (35.7 %) in the COVID-19 patient groups, mainly those treated with antibiotics. A relatively high percentage of Streptococcus was detected in COVID-19 patient groups with obesity or other comorbidities. Respiratory pathogens, including Staphylococcus aureus, Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Salmonella species, along with Pneumocystis jirovecii fungal species were detected by RT-PCR mainly in the COVID-19 patients. Klebsiella pneumoniae was commonly found in most of the samples from the control and COVID-19 patients. Four COVID-19 patients had viral coinfections with human adenovirus, human rhinovirus, enterovirus, and human parainfluenza virus 1. Conclusions: Overall, no substantial difference was observed in the predominant NP bacterial community, but specific taxa were significantly changed between the healthy control and COVID-19 patients. Comparatively, an increased number of respiratory pathogens were identified in COVID-19 patients, and NP colonization by K. pneumoniae was probably occurring in the local population.